Nanoscale metal-organic frameworks for the delivery of nucleic acids to cancer cells - Xue Li; Morgan Chandler; Yelixza I. Avila; Sandra I. Arroyo-Becker; Gilles Patriarche; Antonio Vargas-Berenguel; Juan M. Casas-Solvas; Kirill A. Afonin; Ruxandra Gref (Elsevier, 2023)
Therapeutic nucleic acids (TNAs) are gaining increasing interest in the treatment of severe diseases including viral infections, inherited disorders, and cancers. However, the efficacy of intracellularly functioning TNAs is also reliant upon their delivery into the cellular environment, as unmodified nucleic acids are unable to cross the cell membrane mainly due to charge repulsion. Here we show that TNAs can be effectively delivered into the cellular environment using engineered nanoscale metal-organic frameworks (nanoMOFs), with the additional ability to tailor which cells receive the therapeutic cargo determined by the functional moieties grafted onto the nanoMOF's surface. This study paves the way to integrate the highly ordered programmable nucleic acids into larger-scale functionalized nanoassemblies.